Giant cell arteriitis – a changing entity (Swiss Medical Weekly, 2011)
Giant cell arteriitis (GCA) is the most common of the vasculitis syndromes and, being a disease of the elderly, its incidence is increasing with the general ageing of the population. GCA is most feared for its early complications, namely blindness and stroke, resulting from inflammation and subsequent occlusion of ocular and extra cranial arteries, respectively. More recently, however, GCA has been recognised to also affect limb arteries and the aorta with a high prevalence. These newly recognised features of GCA pose diagnostic, therapeutic and prognostic challenges to treating physicians. Here, recent developments in the field of GCA are summarised and discussed.